Serological Detection of Peste des Petits Ruminants Virus (PPRV) in Sheep and Goats of Muzaffargarh District in South Punjab, Pakistan. Issue 3 (2016) - Yousaf, Farooq; Anwar, Naveed; Abubakar, Muhammad
No abstract available